Misreading the Bengal Delta Climate Change, Development, and Livelihoods in Coastal​ Bangladesh - Dewan, Camelia (Culture, Place, and Nature, 2021)
"Open access edition: DOI 10.6069/9780295749624 Perilously close to sea level and vulnerable to floods, erosion, and cyclones, Bangladesh is one of the top recipients of development aid earmarked for climate change adaptation. Yet, to what extent do adaptation projects address local needs and concerns? Combining environmental history and ethnographic fieldwork with development professionals, rural farmers, and landless women, Misreading the Bengal Delta critiques development narratives of Bangladesh as a "climate change victim." It examines how development actors repackage colonial-era modernizing projects, which have caused severe environmental effects, as climate-adaptation solutions. Seawalls meant to mitigate against cyclones and rising sea levels instead silt up waterways and induce drainage-related flooding. Other adaptation projects, from saline aquaculture to high-yield agriculture, threaten soil fertility, biodiversity, and livelihoods. Bangladesh's environmental crisis goes beyond climate change, extending to coastal vulnerabilities that are entwined with underemployment, debt, and the lack of universal healthcare. This timely book analyzes how development actors create flawed causal narratives linking their interventions in the environment and society of the Global South to climate change. Ultimately, such misreadings risk exacerbating climatic threats and structural inequalities. Misreading the Bengal Delta is available in an open access edition through the Sustainable History Monograph Pilot, thanks to the generous support of the Andrew W. Mellon Foundation."